2023
DOI: 10.3390/antibiotics12091395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous Kidney Replacement Therapy and Hemoadsorption with CytoSorb on Antimicrobial Drug Removal in Critically Ill Children with Septic Shock: A Single-Center Prospective Study on a Pediatric Cohort

Gabriella Bottari,
Bianca Maria Goffredo,
Marco Marano
et al.

Abstract: Background: Extracorporeal therapies (ET) are increasingly used in pediatric settings as adjuvant therapeutic strategies for overwhelming inflammatory conditions. Although these treatments seem to be effective for removing inflammatory mediators, their influence on antimicrobials pharmacokinetic should not be neglected. Methods: A prospective observational study of children admitted to the pediatric intensive care unit (PICU) with a diagnosis of sepsis/septic shock. All critically ill children received hemoads… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…A PK model assessing whether meropenem CL was affected by CytoSorb treatment in 25 critically ill patients found a negligible impact with an increase < 3.7% (Liebchen et al, 2021). Similarly, a prospective observational study carried out in ten critically ill patients undergoing hemoadsorption treatment with CytoSorb reported that drug CL was increased by 43% for ceftazidime and decreased by 57% for meropenem (Bottari et al, 2023). In regard to the use of oXiris high-adsorbent membrane, a prospective population PK study was conducted among 12 critically ill patients treated with meropenem at a dosage of 1000 mg every 8 hours (Padulleś Zamora et al, 2019).…”
Section: Pharmacokinetic Alterations Of Betalactams Associated With P...mentioning
confidence: 98%
See 1 more Smart Citation
“…A PK model assessing whether meropenem CL was affected by CytoSorb treatment in 25 critically ill patients found a negligible impact with an increase < 3.7% (Liebchen et al, 2021). Similarly, a prospective observational study carried out in ten critically ill patients undergoing hemoadsorption treatment with CytoSorb reported that drug CL was increased by 43% for ceftazidime and decreased by 57% for meropenem (Bottari et al, 2023). In regard to the use of oXiris high-adsorbent membrane, a prospective population PK study was conducted among 12 critically ill patients treated with meropenem at a dosage of 1000 mg every 8 hours (Padulleś Zamora et al, 2019).…”
Section: Pharmacokinetic Alterations Of Betalactams Associated With P...mentioning
confidence: 98%
“…Finally, the pharmacokinetics of beta-lactams may be affected also by systems providing renal replacement therapy, removing endotoxins, and adsorbing cytokines even simultaneously, namely CytoSorb hemoadsorption device, oXiris hemofilter, or the Molecular Adsorbent Recirculating System (MARS), which are important supportive tools in patients with severe liver failure or OLT recipients (Isoniemi et al, 2005;Li et al, 2022;Bottari et al, 2023;Popescu et al, 2023). Although no specific study was conducted in the setting of OLT recipients, interesting data may be retrieved by preclinical studies and by clinical studies conducted in other settings of critically ill patients.…”
Section: Pharmacokinetic Alterations Of Betalactams Associated With P...mentioning
confidence: 99%